Canoeing training systems in Russia and Belarus: comparative analysis - Pogrebnoy, A. I.; Makarova, G. A.; Chernukha, S. M.; Karpov, A. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to make a comparative analysis of the canoeing elite training systems in Russia versus Belarus in view of the great competitive accomplishments of the Belarus canoeing elite in the top-ranking events for the last five years. Methods and structure of the study. We have analyzed, for the purposes of the study, the following: more than 50 foreign and national study reports; individual Russian canoeing elite training system for three years (2014-2016) versus that of the Belarus canoeing elite training system accessible in the reference literature. Results and conclusion. The comparative analysis found a few differences in the national canoeing elite training system which contributions to the actual competitive progress cannot be fairly rated in fact (with the analysis being further complicated by the data being not always reported on a yearly basis). Regardless of the training system designs as such, it is still difficult to analyze the contributions of the Russian/ Belarusian canoeing elite training system differences in the competitive progresses. We believe, however, that the following training system design provisions deserve special attention: the Belarusian canoeing elite shows an expressed wavelike workout management pattern with the training system individualization service that is very important. Our analysis of the relevant reported foreign and domestic canoeing elite experiences for the last few years showed that some other training and competitive progress factors with their contributions need to be respected by the national canoeing elite training systems.